Pengaruh Arus Kas Operasi, Leverage dan Pertumbuhan Laba terhadap Kualitas Laba - Indawati Indawati; Rif’atul Huda (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the effect of operating cash flow, leverage, and earnings growth on earnings quality in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study employs a quantitative approach using secondary data obtained from the companies’ published annual financial statements. The sample selection is conducted using purposive sampling based on specific criteria relevant to the research objectives. The analytical method applied is panel data regression with the selection of the Common Effect Model (CEM) after conducting appropriate model selection tests. The results indicate that, partially, operating cash flow and leverage have a positive and significant effect on earnings quality. This suggests that a company’s ability to generate cash from its operational activities and manage its capital structure plays an important role in determining the quality of its earnings. Meanwhile, earnings growth does not have a significant effect on earnings quality, indicating that an increase in earnings does not necessarily reflect higher earnings quality. However, simultaneously, operating cash flow, leverage, and earnings growth are found to have a significant effect on earnings quality. These findings imply that earnings quality is more influenced by operational performance and financing structure rather than earnings growth alone. Therefore, this study is expected to contribute to the development of accounting literature and serve as a consideration for investors and management in making more informed economic decisions.